Qualitative Assessment of Media Influence on the 2022 World Cup in Qatar - BALLAH YOUSSOUF, Youssouf; ADAMU MAMMAN, Musa (Revue Internationale des Sciences de Gestion, 2024)
This qualitative study explores the impact of media criticism on the 2022 FIFA World Cup, with a particular focus on the French context. While Qatar, as the host country, is already at the center of debates, no contemporary edition of the global tournament has sparked as much criticism and controversy, in addition to concerns related to the organization of the event. Our analysis is distinguished by combining an in-depth study of the content of French-language print media corpora with descriptive statistical treatments aimed at quantifying television audiences for matches involving the French national team during the 2018 and 2022 World Cups. To achieve this, we selected five newspaper articles for a content analysis and compared the television audiences of seven matches from the 2018 World Cup with those of seven matches from the 2022 World Cup. The results of the first study identified seven main themes that prevailed in the content of French-language media, shedding light on the key topics of discussion surrounding the event. The second study revealed a significant increase in television audiences for the 2022 World Cup compared to the previous edition. These results indicate that despite numerous criticisms, the spectacle of the World Cup remains extremely popular. This research thus provides an in-depth insight into how media criticism influences the consumption of global football, highlighting the resilience and continued appeal of this major event.